Autonomous Microrobotic Manipulation Using Visual Servo Control - Feemster, Matthew (Micromachines (Basel), 2020)
This describes the application of a visual servo control method to the microrobotic manipulation of polymer beads on a two-dimensional fluid interface. A microrobot, actuated through magnetic fields, is utilized to manipulate a non-magnetic polymer bead into a desired position. The controller utilizes multiple modes of robot actuation to address the different stages of the task. A filtering strategy employed in separation mode allows the robot to spiral from the manipuland in a fashion that promotes the manipulation positioning objective. Experiments demonstrate that our multiphase controller can be used to direct a microrobot to position a manipuland to within an average positional error of approximately 8 pixels (64 µm) over numerous trials.